Governance Gaps in Managing Tourism Potential: A Case Study Of Loyok Village, East Lombok Regency - Amrullah; Muhammad Arif Febrian; Zainul Abidin; Faris Yoga Pratama; Baiq Nadia Tiara Rizki; Nely Harfina (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
This study aims to analyse the limitations of the role of the Loyok Village government in managing the potential of a cultural tourism village based on bamboo handicrafts, as well as to understand institutional dynamics and the conditions of local actors in tourism development. Loyok Village is known as a centre of bamboo craftsmanship in East Lombok; however, tourism management in the village has not yet operated optimally. The research employs a qualitative method with a case study approach, involving village officials, artisans, and tourism actors as informants selected through purposive and snowball sampling techniques. Data were collected through in-depth interviews, limited participant observation, and document analysis, then analysed using data reduction, data display, and conclusion drawing, with source triangulation to ensure validity.The findings reveal that the village government does not yet have adequate regulations, including the absence of a Village Regulation specifically on tourism villages, which results in ineffective coordination, guidance, and facilitation functions. Institutions such as BUMDes and Pokdarwis have also not played an optimal role, while tourism development instead relies heavily on the self-reliance of artisans. Tourist visits occur in an unstructured manner, economic benefits are unevenly distributed, and the regeneration of artisans faces challenges due to low interest among the younger generation. The study concludes that weak governance and limited coordination among actors are the main factors hindering the development of Loyok Village as a sustainable cultural tourism village.